Optimal Materialized View Management in Distributed Environment Using Random Walk Approach - Bagale, Purushottam; Joshi, Shashidhar Ram (Journal of Advanced College of Engineering and Management, 2016)
Materialized View selection and maintenance is a critical problem in many applications. In large databases particularly in distributed database, query response time plays an important role as timely access to information and it is the basic requirement of successful business application. The materialization of all views is not possible because of the space constraint and maintenance cost constraint. Materialized views selection is one of the crucial decisions in designing a data warehouse for optimal efficiency. Selecting a suitable set of views that minimizes the total cost associated with the materialized views is the key component in distributed database environment. Several solutions have been proposed in the literature to solve this problem. However, most studies do not encompass search time, storage constrains and maintenance cost. In this research work two algorithms are depicted; first for materialized view selection and maintenance in distributed environment where database is distributed, Second algorithm is for node selection in distributed environment. Journal of Advanced College of Engineering and Management, Vol.1, 2015, 69-75